Isolation of Yokenella regensburgei ("Koserella trabulsii") from a patient with transient bacteremia and from a patient with a septic knee. - Abbott, S L (1994)
Yokenella regensburgei ("Koserella trabulsii") was isolated from a 74-year-old male with a septic knee and from a 35-year-old immunocompromised female whose transient bacteremia occurred without overt signs of sepsis. Neither strain was correctly identified by laboratories using a variety of techniques.